1989
DOI: 10.1042/bj2580663
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plasma acute-phase protein and albumin levels in the liver of scalded rats

Abstract: At 12 h after scalding of rats a doubling of the hepatocyte nuclear DNA content, which arose from the presence of additional complete genomes and not from amplification of genes coding for the major acute-phase proteins or albumin, was observed. Examination of relative transcription rates per control DNA mass revealed that alpha 1-acid-glycoprotein and cysteine-proteinase-inhibitor genes remained constitutive, alpha- and gamma-fibrinogen and haptoglobin genes underwent transcriptional activation for 290 and 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
6

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
2
12
0
6
Order By: Relevance
“…This process reaches its peak in 12-24 h. Albumin has clearly been shown to leak from the intravascular space during at least the first 6-18 h after injury [17,18]. Besides, examination of the livers of burned animals reveals that the messenger RNA for albumin is decreased in response to injury [19,20], a response that is associated with the increase in acute phase reactants. After burn shock, therefore, serum albumin levels would continue to decrease because of decreased production and ongoing losses through the wound.…”
Section: Discussionmentioning
confidence: 99%
“…This process reaches its peak in 12-24 h. Albumin has clearly been shown to leak from the intravascular space during at least the first 6-18 h after injury [17,18]. Besides, examination of the livers of burned animals reveals that the messenger RNA for albumin is decreased in response to injury [19,20], a response that is associated with the increase in acute phase reactants. After burn shock, therefore, serum albumin levels would continue to decrease because of decreased production and ongoing losses through the wound.…”
Section: Discussionmentioning
confidence: 99%
“…The control animals were routinely injected with pyrogen-free saline. The animals were killed 24 h after the initial treatment, when maximal transcription of the rat haptoglobin gene is established (13). Until their death, the rats were kept at constant temperature, humidity, and dark/light intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, by bringing together speci c DNA sequences and transactivator proteins, the nuclear matrix organizes and stabilizes the DNA in a speci c 3-dimensional conformation that consequently determines tissue-speci c gene expression (6). In the course of studying the dynamics of nuclear matrix-DNA interactions, we observed that the increased rate of transcription of the rat haptoglobin gene during the acute-phase (AP) response (13) was accompanied by an increased binding of its anking 5 0 region to the nuclear matrix (14). This was mediated by a MAR-like, 38-base-long adenine tract lying 147 bp upstream from the cis-element (¡ 165/¡ 56).…”
Section: Introductionmentioning
confidence: 99%
“…After acute systemic tissue injury, transcription of the Hp gene, mRNA concentration, Hp protein synthesis, and plasma concentration are increased three-to sixfold (1,33,47). The principal acute-phase mediators for hepatic Hp regulation in human cell systems have been identified as interleukin-6 (IL-6) and glucocorticoids (7,12,18,37).…”
mentioning
confidence: 99%